A Decade of Fuel Price Fluctuations: The Trend and Their Inflationary Effects in Nigeria (2014-2024) - Alfred Ayo Ayenigba (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study examines the decade-long (2014–2024) relationship between petrol price fluctuations and inflation in Nigeria, a petroleum-dependent economy grappling with fuel subsidy reforms, currency instability, and global oil market shocks. Leveraging quantitative analysis of annual data from the National Bureau of Statistics (NBS), Central Bank of Nigeria (CBN), and Nigerian National Petroleum Corporation (NNPC), the research employs time series trend analysis, Pearson’s correlation (r = 0.93), and linear regression modeling ( ​) to reveal that petrol price changes explain 87.1% of inflation variance (R2=0.871). The 2023 total subsidy removal triggered catastrophic spikes, with petrol prices surging 300% (₦617 to ₦1,030/liter) and inflation peaking at 34.8% in 2024, disproportionately burdening low-income households and SMEs. Policy recommendations advocate fazed subsidy removal paired with social safety nets, renewable energy investments to reduce petrol dependency, and modular refinery development to curb import costs. This study provides a framework for mitigating fuel-driven inflation in resource-dependent economies.